Precise tuning of gene expression levels in mammalian cells - Yale S. Michaels (Nature Portfolio, 2019)
Analogue regulation of gene expression is important for normal function in mammals but existing genetic technologies are designed to achieve ON/OFF control. Here the authors develop synthetic microRNA silencing-mediated fine-tuners (miSFITs) to precisely control target gene expression levels.